1997
DOI: 10.1159/000291852
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Gestrinone after Surgery in Treatment of Endometriosis

Abstract: Objective: The clinical and histological efficacy of gestrinone in the treatment of endometriosis was evaluated. Methods: A prospective study was performed with longitudinal follow-up of 4 years duration (minimum) for each patient. Twenty-five cases of endometriosis were treated with gestrinone (as a drug of choice or associated with other local surgical treatment) during 6 months. Results: The total or partial response to pain was induced with treatment in 19 of the 20 cases (95%), and posttreatment pregnanci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…Gestrinone was developed originally as a long-acting contraceptive. Because of its marked inhibitory effects on ER and PR in the endometrium and uterus, gestrinone has also been clinically applied to treat endometriosis and uterine leiomyoma with success [27,28] . Marca et al demonstrated that gestrinone significantly increased blood flow impedance of the uterine artery [29] .…”
Section: Introductionmentioning
confidence: 99%
“…Gestrinone was developed originally as a long-acting contraceptive. Because of its marked inhibitory effects on ER and PR in the endometrium and uterus, gestrinone has also been clinically applied to treat endometriosis and uterine leiomyoma with success [27,28] . Marca et al demonstrated that gestrinone significantly increased blood flow impedance of the uterine artery [29] .…”
Section: Introductionmentioning
confidence: 99%